Numerical investigation of seismic performance of high modulus columns under earthquake loading - Demir, Selcuk; Ozener, Pelin (SPRINGER, 2019)
This paper presents the result of two-dimensional finite element modeling studies in order to investigate the seismic behavior of high modulus columns in liquefiable soil. Particular attention was paid to the shear stress reduction mechanism of the high modulus columns and the shear strain distribution between soil and columns during earthquake motion. Numerical analyses were performed using a nonlinear elasto-plastic model in Plaxis 2016. The reliability of the numerical simulations was verified through the results of a centrifuge test model designed to investigate the contribution of high modulus columns in liquefaction mitigation. The capability of numerical simulations was assessed primarily through comparison of predicted acceleration-time histories, pore water pressures, and displacements with the measured counterparts. The results of the numerical analysis showed that the presence of the columns did not reduce seismic shear stresses in the soil when compared to the unimproved soil condition and pure shear behavior between soil and column did not develop as expected in the current design methodology.
Keywords: liquefaction; high modulus column; soil improvement; UBC3D-PLM; Engineering